Holographic data storage and display by PANDA ring resonator technique - Phetcharat, V.; Thammawongsa, N.; Somsuk, K.; Jamsai, M.; Yupapin, P. P. (My University, 2014)
In this paper, a novel method of holographic data storage and display was demonstrated. The use of nonlinear optical device called PANDA ring resonator is realized by Whispering Gallery Mode (WGM) and manipulated by Phase Conjugate Mirror (PCM) techniques. The result shown that the proposed model was performed a 3×3 optical waveguide holographic matrix which manipulated with a various wavelength and can be well applied to dynamic holographic optical data storage, holographic display, and other applications by compact nonlinear optical device. © (2014) Trans Tech Publications, Switzerland.
Keywords: Holographic data storage; Holographic display; Ring resonator; Whispering gallery mode